Early Christianity and Ancient Astrology - Hegedus, Timothy (Patristic Studies, 2007)
Early Christianity and Ancient Astrology explores a variety of responses to astrology, the most popular form of divination among early Christians in Greco-Roman antiquity. After a brief overview of ancient astrological theory and a survey of polemical responses to it, this book documents instances in which early Christian writers and communities incorporated astrology positively into their beliefs and practices. This study is of interest to students of early Christianity and of Greco-Roman religion and to those concerned with interfaith relations or with issues of Christian unity and diversity. It is particularly recommended for use in courses on the history of Christianity and on the religions of Greco-Roman antiquity.